NEW BIOKERATOPROSTHETIC COMPLEX BASED ON MODIFIED ALLOGENIC DONOR CORNEAS AND CULTURED POSTNATAL HUMAN SKIN FIBROBLASTS - S. A. Borzenok; A. V. Vasilyev; A. V. Shipunova; E. B. Dashinimaev; Z. I. Moroz; Y. A. Komakh; E. V. Kovshun (Вестник трансплантологии и искусственных органов)
The aim of the study was to develop biokeratoprosthetic complex based on cross-linking modified allogenic donor corneas and cultured postnatal human skin fibroblasts. Cross-linking enhances corneal strength and tole- rance to proteolytic enzymes. Fibroblasts’ proliferation and migration in the intrastromal pocket stimulates fiber syncytium formation and collagen microcarriers integration into the corneal stroma, as well as intercellular ma- trix formation around the prosthetic metallic plate as early as the cocultivation stage. A new biokeratoprosthetic complex has been successfully developed for further in vivo studies.